Response of Jupiter's inner magnetosphere to the solar wind derived from extreme ultraviolet monitoring of the Io plasma torus. Issue 24 (20th December 2016) - Murakami, Go; Yoshioka, Kazuo; Yamazaki, Atsushi; Tsuchiya, Fuminori; Kimura, Tomoki; Tao, Chihiro; Kita, Hajime; Kagitani, Masato; Sakanoi, Takeshi; Uemizu, Kazunori; Kasaba, Yasumasa; Yoshikawa, Ichiro; et al.
Abstract: Because Jupiter's magnetosphere is huge and is rotationally dominated, solar wind influence on its inner part has been thought to be negligible. Meanwhile, dawn‐dusk asymmetric features of this region have been reported. Presence of dawn‐to‐dusk electric field is one of the leading explanations of the asymmetry; however, the physical process of generating such an intense electric field still remains unclear. Here we present long and continuous monitoring of the extreme ultraviolet emissions from the Io plasma torus in Jupiter's inner magnetosphere made by the Hisaki satellite between December 2013 and March 2014. We found five occasions where the dusk/dawn brightness ratio was enhanced above 2.5 in response to rapid increase of the solar wind dynamic pressure. The enhancement is achieved as the dusk region brightens and the dawn region dims. The observation indicates that dawn‐to‐dusk electric field in the inner magnetosphere is enhanced under compressed conditions. Plain Language Summary: Jupiter has the strongest "barrier" against the solar wind in the solar system‐‐that is, a magnetosphere generated by its strong magnetic field and rapid planetary rotation rate. While it would be natural to think that the inner part embedded deep inside the huge magnetosphere is free of influences of the solar wind flowing around the boundary, there are some puzzling features that are not consistent with this idea. This article describes the clear evidence for the influence of solar wind deep inside Jupiter's magnetosphere. The fundamental question is addressed and is now being answered thanks to long‐term and continuous monitoring in the extreme ultraviolet spectral range obtained by the Earth‐orbiting spectroscope EXCEED. The new capability is helps to more clearly describe how Jupiter's magnetosphere behaves at time‐scales of week to month. Our observation successfully detected the responses to the solar wind in Jupiter's inner magnetosphere. The best example is reported here: it enabled us to give end to the argument that could have lasted for ever. Key Points: The solar wind influence on the Io plasma torus brightness is detected by Hisaki Long‐term monitoring revealed that enhanced dawn‐dusk brightness ratio is seen when solar wind dynamic pressure increased Our result suggests that solar wind influences the dawn‐to‐dusk electric field in Jupiter's inner magnetosphere